Induction of aggression and anxiety-like responses by perfluorooctanoic acid is accompanied by modulation of cholinergic- and purinergic signaling-related parameters in adult zebrafish (2022)
Perfluorooctanoic acid (PFOA) is a contaminant of global concern owing to its prevalent occurrence in aquatic and terrestrial environments with potential hazardous impact on living organisms. Here, we investigated the influence of realistic environmental concentrations of PFOA (0, 0.25, 0.5, or 1.0 mg/L) on relevant behaviors of adult zebrafish (Danio rerio) (e.g., exploration to novelty, social preference, and aggression) and the possible role of PFOA in modulating cholinergic and purinergic signaling in the brain after exposure for 7 consecutive days. PFOA significantly increased geotaxis as well as reduced vertical exploration (a behavioral endpoint for anxiety), and increased the frequency and duration of aggressive episodes without affecting their social preference. Exposure to PFOA did not affect ADP hydrolysis, whereas ATP and AMP hydrolysis were significantly increased at the highest concentration tested. However, AChE activity was markedly decreased in all PFOA-exposed groups when compared with control. In conclusion, PFOA induces aggression and anxiety-like behavior in adult zebrafish and modulates both cholinergic and purinergic signaling biomarkers. These novel data can provide valuable insights into possible health threats related to human activities, demonstrating the utility of adult zebrafish to elucidate how PFOA affects neurobehavioral responses in aquatic organisms.